Prevalence and Severity of High Blood Pressure Among Children Based on the 2017 American Academy of Pediatrics Guidelines - Sharma, Atul K. (JAMA Pediatr, 2018)
IMPORTANCE: Based on the new 2017 blood pressure guidelines, the prevalence of high blood pressure (BP) among adults has increased from 32% to 46%. Based on new norms and diagnostic thresholds that better align with adult definitions, new clinical practice guidelines were also published for children. The American Academy of Pediatrics clinical practice guidelines for the management of elevated BP in children replace the 2004 fourth report from the National Heart, Lung, and Blood Institute. OBJECTIVES: To assess the consequences of the American Academy of Pediatrics clinical practice guidelines for the management of elevated BP in children on the prevalence and severity of elevated BP among children and to characterize risk factors for children with new-onset hypertension or a worsening in clinical stage (“reclassified upward”). DESIGN, SETTING, AND PARTICIPANTS: This study applied both sets of guidelines to classify BP in 15 647 generally healthy, low-risk children aged 5 to 18 years from National Health and Nutrition Examination Surveys (from January 1, 1999, to December 31, 2014). In the case-control portion of the study, children whose BP was reclassified upward (cases) were matched for sex, age, and height with controls with normal BP. Anthropometric and laboratory risk factors were compared, and age- and sex-specific z scores for weight, waist circumference, and body mass index were calculated. Blood pressure was measured by auscultation by trained personnel. After the child rested quietly for 5 minutes, 3 to 4 consecutive BP readings were recorded. MAIN OUTCOMES AND MEASURES: Blood pressure percentiles and clinical classification based on either the 2017 American Academy of Pediatrics guidelines or the 2004 National Heart, Lung, and Blood Institute report. RESULTS: Among the 15 647 children in the study (7799 girls and 7848 boys; mean [SD] age, 13.4 [2.8] years), based on the American Academy of Pediatrics guidelines, the estimated (weighted) population prevalence of elevated BP increased from 11.8% (95% CI, 11.1%-13.0%) to 14.2% (95% CI, 13.4%-15.0%). Overall, 905 of 15 584 children (5.8%) had newly diagnosed hypertension (n = 381) or a worsening in clinical stage (n = 524), which represents a substantial increase in disease burden for the health care system. Children whose BP was reclassified upward were more likely to be overweight or obese, with higher z scores for weight, waist circumference, and body mass index. The prevalence of abnormal laboratory test results was also increased, with adverse lipid profiles and increased hemoglobin A(1c) levels (prediabetes). CONCLUSIONS AND RELEVANCE: Clustering of cardiovascular risk factors in otherwise healthy US children suggests that those whose BP was reclassified represent a high-risk population whose cardiovascular risk may previously have been underestimated.